Underwater Gliders: A Review - Javaid Muhammad Yasar; Ovinis Mark; Nagarajan T; Hashim Fakhruldin B M (MATEC Web of Conferences, 2014)
Underwater gliders are a type of underwater vehicle that transverse the oceans by shifting its buoyancy, during which its wings develop a component of the downward motion in the horizontal plane, thus producing a forward force. They are primarily used in oceanography sensing and data collection and play an important role in ocean research and development. Although there have been considerable developments in these gliders since the development of the first glider concept in 1989, to date, no review of these gliders have been done. This paper reviews existing underwater gliders, with emphasis on their respective working principles, range and payload capacity. All information on gliders available in the public domain or published in literature from the year 2000-2013 was reviewed. The majority of these gliders have an operational depth of 1000 m and a payload of less than 25 kg. The exception is a blend-body shape glider, which has a payload of approximately 800 kg and an operational depth around about 300 m. However, the commercialization of these gliders has been limited with only three know examples that have been successfully commercialized.